Kajian Bentuk dan Makna Lagu “Aut Boi Nian” pada Film Toba Dreams - Irma Pratiwi Samosir; Pulumun Ginting; Wiflihani Wiflihani (Universitas Negeri Medan, 2019)
The purpose of this research is to know the form of Aut Boi Nian songs, to know the meaning contained in the lyrics of Aut Boi Nian songs, to know the relevance of Aut Boi Nian songs with Toba Dreams movie scenes. The theory used in this research is the theory of study that explains the definition of the study or describes a detailed. Theory of music is a cultural activity that is very familiar with human life. Theory of form is a complete scheme or arrangement of several phrases, the theory of meaning that uses the theory of semiotics. The method in this research is descriptive qualitative method where the data is examined through data collection in the form of beam notation, scientific papers, expert opinions, and electronics (Video) whose material is based on the topic of this research. This study choose the location at the Music Laboratory, Building A 2nd Floor of the Faculty of Languages and Arts State University of Medan. In this study the authors did not use the population but directly took samples of the song lyrics Aut Boi Nian and Toba Dreams movie pieces. Based on the results of research conducted it can be seen that the form of the song from Aut Boi Nian is a two-part song form that is A-A '-B-B’. Form A consists of the question phrase and answer phrase, the form A 'consists of the question phrase and answer phrase. Form B consists of the question phrase and answer phrase, the form B 'consists of the question phrase and answer phrase. The meaning contained in the Aut Boi Nian songs is telling of a love story that is too love a woman who ultimately choose another man because of economic factors. The relevance of Aut Boi Nian songs with Toba Dreams movie scenes is not too related to all the scenes in the movie but only in some scenes only.